Better Students Ask More Questions.
please show steps to solve: g(x)= (1/2) for g(x)=(x)^2 + 3(x) +4
1 Answer | add yours
High School Teacher
So you have `1/2=x^2+3x+4 implies x^2+3x+7/2=0`
Now you use formula for solution of quadratic equation
`x_(1,2)=(-b pm sqrt(b^2-4ac))/(2a)` where `a,` `b` and `c` are coefficients of general quadratic equation `ax^2+bx+c=0.`
` x_(1,2)=(-3 pm sqrt(3^2-4cdot7/2))/(2)=(-3 pm sqrt(-5))/(2) = `
` (-3 pm i sqrt(5))/(2) `
Posted by tiburtius on October 28, 2012 at 8:25 PM (Answer #1)
Related QuestionsSee all »
Join to answer this question
Join a community of thousands of dedicated teachers and students.